Exportaciones de Colombia : el valor agregado como una oportunidad de éxito para el futuro de la economía colombiana - Córdoba Cuesta, Luisa Fernanda (Ciencias Administrativas, Económicas y Contables, 2018)
This article addresses the issue of Colombian exports, with the main objective of analyzing through the updated information review, the state of the export sector in terms of diversification of export supply and added value that offers the country in the international market, based on an emblematic product of the nation such as banana. Additionally, it makes a general study of the export sector through data and real experiences, that allow to get closer to the reality of Colombian international trade; with the final conclusion that the Colombian economy still bases its export supply on primary products that don’t offer a differentiating factor and that is necessary for the country, to promote efforts to technify the processes and train the workforce, to achieve innovating through products with added value that can be competitive in the international scene and that represents a better future scenario for the Colombian economy in general